2012
DOI: 10.1021/ie300230k
|View full text |Cite
|
Sign up to set email alerts
|

Facile Method for Determination of Amine Speciation in CO2 Capture Solutions

Abstract: A simple and quantitatively reliable method for determination of amine speciation is introduced. The method employs three experimental methods that should be readily accessible. The results for CO 2 loaded aqueous solutions of 30 wt % monoethanolamine (MEA) are used for demonstration of the method and show promising agreement with the more complicated spectroscopic methods reported in the literature. The measurements were done at ambient temperature and atmospheric pressure, since theoretical calculations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 26 publications
6
62
0
1
Order By: Relevance
“…No characteristic modes for bicarbonate or carbamates were observed at CO 2 concentrations between 0–2500 ppm; these modes became apparent only weakly and only upon significantly raising the CO 2 level to 1–10% (i.e., 10 000–100 000 ppm; Figure S14). Analogous to the speciation of dissolved CO 2 in aqueous amine media, 45 the bicarbonate and carbamate salt fractions in Cu 3 HIB 2 are presumed to be exceedingly small, particularly at typical ambient CO 2 levels. Most revealingly, increasing CO 2 levels cause a gradual decrease of the background IR absorbance of the material, most evident in the spectral ranges that are not dominated by strong vibrational modes from the MOF itself (e.g., h v = 0.5–0.6 eV and 0.25–0.3 eV).…”
Section: Resultsmentioning
confidence: 99%
“…No characteristic modes for bicarbonate or carbamates were observed at CO 2 concentrations between 0–2500 ppm; these modes became apparent only weakly and only upon significantly raising the CO 2 level to 1–10% (i.e., 10 000–100 000 ppm; Figure S14). Analogous to the speciation of dissolved CO 2 in aqueous amine media, 45 the bicarbonate and carbamate salt fractions in Cu 3 HIB 2 are presumed to be exceedingly small, particularly at typical ambient CO 2 levels. Most revealingly, increasing CO 2 levels cause a gradual decrease of the background IR absorbance of the material, most evident in the spectral ranges that are not dominated by strong vibrational modes from the MOF itself (e.g., h v = 0.5–0.6 eV and 0.25–0.3 eV).…”
Section: Resultsmentioning
confidence: 99%
“…The use of titration 35,32 and FTIR for mechanistic studies has been reported 29,36-38 but quantification and real time / flow unit identification of unexpected species is cumbersome. Herein, in-situ 13 C and 1 H NMR spectroscopy using a built-in micro reactor was used to provide real time insights on reaction mechanisms and product speciation under various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy in CO 2 loading was less than 5.61 %, indicating reasonable reliability of the results obtained. The reliability and the repeatability (RSD = 2.27 %) were confirmed by comparison with literature data [13,14] where, besides the gas phase analysis (chromatographic gas analysis), the liquid phase analysis (titration of the CO 2 -loaded amine solutions, nuclear magnetic resonance (NMR) spectroscopy, Fourier transform infrared (FTIR) technique) was applied. The pH of the solution was measured with a pH meter (S20 SevenEasy™ pH; Mettler Toledo).…”
Section: Experimental Setup and Proceduresmentioning
confidence: 73%
“…h a a 1 ln a 2 P CO 2 (14) where h a is the CO 2 loading (L CO 2 /L solution), and a 1 (L CO 2 /L solution) and a 2 (bar -1 ) are constants. Eq.…”
Section: Thermodynamic Modelmentioning
confidence: 99%